COMPARISON OF TEMPERATURE VARIATIONS (60˚C, 80˚C, and 100˚C) ON MESH 30 AND 250 DRYING OF COFFEE WOOD CHARCOAL BRIQUETTE ON CALORIAL VALUE AND HARDNESS - Sakerengan , Jamiko; Tugur Redationo , Nereus; Crisanto Putra Mbulu , Bernardus (Universitas Katolik Widya Karya Malang, 2025)
The selection of coffee wood in this study is based on the fact that coffee wood is waste and has not been utilized optimally and the availability of coffee wood is large and easy to obtain in the East Java region. Coffee wood is a type of wood that is not in demand by many people because this wood is relatively small and not straight. To reduce waste, researchers made briquettes made from coffee wood using mesh 30 and 250 with variations in drying temperatures (60 °C, 80 ° C and 100 ° C). After that was carried out Calorimeter Bomb Testing, and hardness. The highest calorific value resulting from temperature variations of 60°C, 80°C, and 100°C mesh 30 and 250 drying coffee wood briquettes is mesh 30 temperature 100°C of 6972.23 cal/g, and mesh 250 temperature 100°C of 6763.19 cal/g. The effect of the ratio of temperature variations (60°C, 80°C and 100°C) mesh 30 and 250 Drying coffee wood briquettes is: Grain and adhesive size. The smaller the grain size on the briquettes, namely mesh 250, it produces a high hardness value of 60 °C of 26.6 HA, a temperature of 80 °C of 27.7 HA, and a temperature of 100 ° C of 27.4 HA, the larger the grain size in the briquette, namely mesh 30, the low hardness value of 60 ° C of 25.6 HA, temperature of 80 ° C of 26.4 HA, and a temperature of 100°C of 26.2 HA. The effect of the adhesive is that when drying the oven for 3 hours with temperature variations (60 ° C, 80 ° C and 100 ° C) makes the adhesive react so that the adhesive evaporates and coagulates which causes the hardness value to rise and fall.